2010
DOI: 10.1111/j.1743-6109.2009.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phosphodiesterase Type 5 Expression and Functional Activity in the Human Male Lower Urinary Tract

Abstract: Introduction Phosphodiesterase type 5 (PDE5) inhibitors ameliorate low urinary tract (LUT) symptoms in men with ED and symptomatic benign prostatic hyperplasia (BPH). PDE5 is highly expressed in rat and human bladder, where it regulates cyclic guanosine monophosphate (cGMP) degradation, muscle tone, and proliferation. Aim To investigate PDE5 tissue distribution and activity in human LUT tissues (urethra, prostate, and bladder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 40 publications
11
128
2
2
Order By: Relevance
“…Our findings are in apparent disagreement with previous data showing high abundance of PDE5 mRNA in the human prostate (Morelli et al 2004) and question the view that androgendependent upregulation leads to generally enhanced PDE5 expression in organs of the male genital tract (Morelli et al 2004). Compatible with our results, however, a recent characterization of PDE5 mRNA distribution in human male lower-urinary tract tissues also revealed lowest abundance in the prostate gland (Fibbi et al 2010). Thus, the weak expression of PDE5 (and probably the other cGMP signaling proteins) in the prostate may not represent a rat-specific phenomenon.…”
Section: Organ-specific Characteristics Of Cgmp Signalingcontrasting
confidence: 57%
See 2 more Smart Citations
“…Our findings are in apparent disagreement with previous data showing high abundance of PDE5 mRNA in the human prostate (Morelli et al 2004) and question the view that androgendependent upregulation leads to generally enhanced PDE5 expression in organs of the male genital tract (Morelli et al 2004). Compatible with our results, however, a recent characterization of PDE5 mRNA distribution in human male lower-urinary tract tissues also revealed lowest abundance in the prostate gland (Fibbi et al 2010). Thus, the weak expression of PDE5 (and probably the other cGMP signaling proteins) in the prostate may not represent a rat-specific phenomenon.…”
Section: Organ-specific Characteristics Of Cgmp Signalingcontrasting
confidence: 57%
“…Compared with lung, where high PDE5 provided a molecular basis for treatment of pulmonary hypertension (Corbin et al 2005), cytosolic PDE5 abundance is similar and membrane concentrations are even higher in the bladder. Immunohistochemical data localized PDE5 to the bladder smooth muscle (Fibbi et al 2010), and both NO donors and PDE5 inhibitors were found to reduce the muscle tonus in experiments with rat and human bladder tissues (Sandner et al 2009), although cAMPmediated pathways appear to play a predominant role for direct detrusor muscle relaxation (Andersson & Arner 2004). Tension release during the bladder filling phase is crucial and requires robust mechanisms to generate smooth muscle relaxation.…”
Section: Organ-specific Characteristics Of Cgmp Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The prostate is an immunocompetent organ, not only because it is populated by resident inflammatory cells, including T-and B-lymphocytes, macrophages, and mast cells (De Marzo et al 2007, Fibbi et al 2010a, but also because stromal prostatic cells can secrete several proinflammatory cytokines and are able to recruit and activate CD4…”
Section: Discussionmentioning
confidence: 99%
“…Primary human prostatic smooth muscle cells (hBPH) were obtained and cultured as previously described (Crescioli et al 2000, Fibbi et al 2010a. Briefly, six different hBPH cell preparations were obtained from prostate tissues derived from six patients who underwent TURP or suprapubic adenomectomy for BPH after informed consent.…”
Section: Human Prostatic Stromal Cell Culturesmentioning
confidence: 99%